(untitled) (Global Journal of Human-Social Science, 2017)
This paper examines the impact of monetary policy on the economic development by using annual time series data from 1989-2016 The unit root testing result suggests that all variables are stationary at first difference therefore the Johansen Cointegration and Error Correction Model has been employed to analyze the association between variables The finding shows that money supply interest rate and inflation rate negatively effect on the real GDP per capita in the long run and only the real exchange rate has a positive sign The error correction model result indicates the existence of short run causality between money supply real exchange rate and real GDP per capita